2021
DOI: 10.1002/slct.202101387
|View full text |Cite
|
Sign up to set email alerts
|

New 1,2,4‐Triazole Scaffolds as Anticancer Agents: Synthesis, Biological Evaluation and Docking Studies

Abstract: A series of novel 4,5-diphenyloxazol-1,2,4-triazole derivatives (6 a-6 l) were synthesized and screened for anticancer activity against the prostate lung cancer cell lines viz., PC-93 and HBT-55. The outcome of the investigation reveals that compounds 6 a, 6 b and 6 j showed potential anticancer activity against PC-93 cell line with the half maximal inhibitory concentration (IC 50 ) values of 13.12, 15.34, and 16.34 μM, respectively. Compounds 6 a, 6 d and 6 j exhibited potential anticancer activity against HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Figure 10 represents commercial drugs carrying 1,2,4-triazole moiety as antifungal, [82] antitumor, [83] estrogen blockers, [84] antidepressant, [85] antihypertensives, [86] herbicides, [87] anticonvulsants, [88] antihypnotics, [89] and plant growth regulators. [90] Kantar et al have reported the preparation and evaluation of novel phthalonitrile and zinc(II) phthalocyanines containing morpholino substituted 1,2,4-triazole-3-one derivatives under microwave irradiation as XO inhibitors, as seen in Figure 11.…”
Section: Significance Of 124-triazole Scaffold As Potent Xo Inhibitorsmentioning
confidence: 99%
“…Figure 10 represents commercial drugs carrying 1,2,4-triazole moiety as antifungal, [82] antitumor, [83] estrogen blockers, [84] antidepressant, [85] antihypertensives, [86] herbicides, [87] anticonvulsants, [88] antihypnotics, [89] and plant growth regulators. [90] Kantar et al have reported the preparation and evaluation of novel phthalonitrile and zinc(II) phthalocyanines containing morpholino substituted 1,2,4-triazole-3-one derivatives under microwave irradiation as XO inhibitors, as seen in Figure 11.…”
Section: Significance Of 124-triazole Scaffold As Potent Xo Inhibitorsmentioning
confidence: 99%
“…69 Besides the 1,2,3-triazole ring, some possible targets of the 1,2,4-triazole compounds were reported such as anti-apoptotic Bcl-2 protein, 77 vascular endothelial growth factor 2 (VEGF2), 78 as well as fibroblast growth factor receptor 1 (FGFR1) and Ser-/Thr-specific kinase Akt protein (Akt). 79 Additionally, the nitrogen atom of the 1,2,4-triazole ring was noted to form coordination interaction with the heme Fe ion of the aromatase enzyme contributing to the aromatase inhibitory effect. 80…”
Section: Roles Of the 123-triazole Ring In Ligand-anticancer Targets ...mentioning
confidence: 99%
“…13,14 After some triazole fungicides are used, plants cannot synthesize auxin and gibberellin (GA), thereby inhibiting plant growth. 15 On the other hand, 1,2,4-triazole derivatives represent attractive agents for synthetic optimization studies with a wide range of biological activities such as herbicidal, 16 antiproliferative, 17,18 antimicrobial, 19,20 anticancer, 21 analgesic, 22 antioxidant, 23,24 antimalarial, 25 and anticoronavirus activities. 26 Triazole fungicides are sterol biosynthesis C-14 demethylase inhibitors (DMI), 27 which have an inhibitory effect on ergosterol biosynthesis in plants and fungi.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Triazole fungicides have high activity, broad spectrum, strong systemic conductivity, and adequate half-lives. , Most triazole fungicides can prevent diseases , and regulate plant growth. , After some triazole fungicides are used, plants cannot synthesize auxin and gibberellin (GA), thereby inhibiting plant growth . On the other hand, 1,2,4-triazole derivatives represent attractive agents for synthetic optimization studies with a wide range of biological activities such as herbicidal, antiproliferative, , antimicrobial, , anticancer, analgesic, antioxidant, , antimalarial, and anticoronavirus activities …”
Section: Introductionmentioning
confidence: 99%